Our Interconnection through Mobility Facilitates the Spread of Infectious Pathogens - Chengjun Sun (Public Health, 2025)
Pathogens have been moving around for a while. The History of the Peloponnesian War, written by Thucydides (c. 460 BC - c. 395 BC), an Athenian historian, describes the plague of Athens of 430 BC, and it is said “It first began in the parts of Ethiopia above Egypt, and thence descended into Egypt and Libya and into most of the [Persian] King’s country. Suddenly falling upon Athens, it first attacked the population in Piraeus [..] and afterwards appeared in the upper city, when the deaths became much more frequent.